2013
DOI: 10.5398/medpet.2013.36.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regional Distribution Capacity and Priorities for Improving Beef Cattle Population in East Nusa Tenggara Province

Abstract: Cattle farms resources in NTT are potential to be developed, but regency has not used it effectively. As a consequently, a huge disparity of beef cattle deployment between regencies occur. NTT sangat potensial untuk dikembangkan, namun belum dimanfaatkan secara efektif oleh setiap kabupaten. Akibatnya, terdapat disparitas penyebaran sapi yang sangat besar antar-kabupaten. Penelitian bertujuan�� a�� Menganalisis tingkat Menganalisis tingkat kapasitas penambahan populasi sapi pada setiap kabupaten; dan b�� Merum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
13
1
2
Order By: Relevance
“…The findings of this study were not in agreement with Lole et al (2013) and Isyanto and Iwan (2016). Both researchers reported that the growth of the beef cattle population in East Nusa Tenggara (NTT) and in Ciamis, West Java, Indonesia, was influenced by the high number of culling and the conversion (reduction) of pastoral land into plantation and settlement land.…”
Section: Pc and CI Contributioncontrasting
confidence: 99%
“…The findings of this study were not in agreement with Lole et al (2013) and Isyanto and Iwan (2016). Both researchers reported that the growth of the beef cattle population in East Nusa Tenggara (NTT) and in Ciamis, West Java, Indonesia, was influenced by the high number of culling and the conversion (reduction) of pastoral land into plantation and settlement land.…”
Section: Pc and CI Contributioncontrasting
confidence: 99%
“…The data of the last 10 years show the production of cattle in the province has grown by 2.2 percent (with a population in 2017 of about 905.326 head) (NTT Disnak, 2018). Approximately 68.5% of cattle population is in West Timor, including the District of Kupang, TTS, TTU, Belu, and Malaka (Yusuf and Nulik, 2009;Lole et al, 2013). The slow growth rate of calves production is simultaneously influenced by factors, such as technical/technology, economy, socio-culture, investment, institutions, and related policies (Lole et al, 2013;Guntoro and Priyadi, 2012;Khan and Iqubal, 2010;Etwire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 68.5% of cattle population is in West Timor, including the District of Kupang, TTS, TTU, Belu, and Malaka (Yusuf and Nulik, 2009;Lole et al, 2013). The slow growth rate of calves production is simultaneously influenced by factors, such as technical/technology, economy, socio-culture, investment, institutions, and related policies (Lole et al, 2013;Guntoro and Priyadi, 2012;Khan and Iqubal, 2010;Etwire et al, 2013). Each of the contributing factors needs to be identified and analyzed for the level of significance and the impact on livestock production rate of calves (Lole et al, 2013;Guntoro et al, 2016;Ajetomobi, 2010;Bunmee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Analisis kapasitas tampung wilayah untuk ternak (KWT) dilakukan untuk melalui perhitunan berdasarkan potensi pakan dan potensi rumah tangga petani. Hasil penghitungan kapasitas tampung tersebut selanjutnya digunakan untuk menentukan kapasitas peningkatan populasi ternak ruminansia (PPTR-Efektif), yaitu nilai terendah dari perbandingan antara kapasitas tampung berdasarkan potensi pakan dengan kapasitas tampung berdasarkan potensi rumah tangga petani (Lole et al, 2013). Persamaan untuk menghitung kapasitas tampung ternak berdasarkan potensi pakan (KWT-pakan) digunakan persamaan sebagai berikut (Arief H et al, 2012) :…”
Section: Analisis Potensi Pakan Hijauan (Rumput Dan Jerami)unclassified
“…dimana : KWT pakan = kemampuan wilayah dalam menampung ternak berdasarkan potensi pakan KH = kebutuhan hijauan setiap satuan ternak per tahun (9,1kg BKx365) PHR = produksi hijauan rumput (ton BK/tahun) PHJ = produksi hijauan jerami (ton BK/tahun) Sedangkan persamaan untuk menghitung kapasitas tampung ternak berdasarkan rumah tangga petani (KWT-kk) adalah sebagai berikut (Lole et al, 2013) : dimana : KWT-kk = kemampuan wilayah dalam menampung ternak berdasarkan potensi rumah tangga petani Ʃ KK = jumlah rumah tangga petani (KK) 2 = indeks kemampuan rumah tangga petani memelihara ternak ruminansia 4. Analisa deskriptif dilakukan terhadap kondisi ekologi yang meliputi luas wilayah, kondisi fisik/tata guna lahan, sarana pendukung, rumah tangga petani/ kelompok tani dan kebijakan tata ruang wilayah (Mei et al, 2004).…”
Section: Analisis Potensi Pakan Hijauan (Rumput Dan Jerami)unclassified